Asuhan Keperawatan Pada Ny. S Dengan Gangguan Sistem Hematologi: Anemia Di Ruang Dahlia RSUD dr. Soeselo Kabupaten Tegal - Abdul Chakim Al Amer; Esti Nur Janah; Wawan Hediyanto (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Anemia is a disease characterized by a decrease in hemoglobin in the body. Hemoglobin is a metalloprotein, a protein containing iron in red blood cells, whose function is to carry oxygen from the lungs to the body (Julia and Amelia, 2018). A patient is said to be anemic if the hemoglobin Hb concentration is less than 13.5 g/dL or the hematocrit is less than 41% in men and 36% in women (SIKI, 2019).